1981
DOI: 10.1126/science.7233198
|View full text |Cite
|
Sign up to set email alerts
|

Transbilayer Phospholipid Asymmetry in Plasmodium knowlesi -Infected Host Cell Membrane

Abstract: The membranes from normal and Plasmodium knowlesi-infected rhesus monkey erythrocytes (90 to 95 percent infected with early ring stage) were analyzed for transbilayer distribution of phosphatidylcholine (PC), phosphatidylethanolamine (PE), and phosphatidylserine (PS), by means of chemical and enzymatic probes. The external monolayer of the normal red cell membrane contained at least 68 to 72 percent of the total phosphatidylcholine and 15 to 20 percent of the total phosphatidylethanolamine. In the infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

1983
1983
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 17 publications
(15 reference statements)
4
29
2
Order By: Relevance
“…PS remained completely inaccessible to either chemical or enzymatic probes during the parasitic invasion (25). These results are quite similar to ours.…”
Section: Discussionsupporting
confidence: 82%
“…PS remained completely inaccessible to either chemical or enzymatic probes during the parasitic invasion (25). These results are quite similar to ours.…”
Section: Discussionsupporting
confidence: 82%
“…58 Roughly 70% of the PC was hydrolyzed in the presence of phospholipase A 2 , while 15-20% of the PE was labeled with TNBS. Because no PS was hydrolyzed or labeled, it was postulated to reside in the inner monolayer.…”
Section: Other Erythrocyte Membranesmentioning
confidence: 99%
“…Because prior studies have shown that endocytosis is accompanied by lipid changes (23,25) but not by protein changes (Schrier SL, unpublished observations) we examined neonatal red cell membrane lipids in considerable detail. Our data agree with earlier reports that the neonatal red cell has a slightly higher cholesterol to phospholipid ratio and a higher sphingomyelin to PC ratio than the adult red cell (10,11,26).…”
Section: Osmotic Gradient Ektacytometrymentioning
confidence: 99%